Light and nutrients regulate energy transfer through benthic and pelagic food chains. Issue 12 (13th April 2015) - Rowland, Freya E.; Bricker, Kelley J.; Vanni, Michael J.; González, María J.
Abstract : The amount of energy flowing to top trophic levels depends on primary production and the efficiency at which it is converted to production at each trophic level. In aquatic systems, algal production is often limited by light and nutrients, and the nutritional quality of algae depends on the relative balance of these two resources. In this study, we used a mesocosm experiment to examine how light and nutrient variation affected food chain efficiency (FCE, defined as the proportion of primary production converted to top trophic level production), using a food web with benthic and pelagic food chains. We also related variation in benthic and pelagic efficiencies to the nutritional quality of primary producers, i.e. carbon:nitrogen:phosphorus stoichiometry. As predicted, pelagic and benthic FCEs were highest under low light/high nutrient conditions, the treatment with the best algal food quality, i.e. the lowest C:nutrient ratios. Pelagic FCE and pelagic herbivore efficiency (HEP ) were more responsive than benthic FCE to variation in light and nutrients. Furthermore, pelagic FCE and HEP were highly correlated with algal C:P, suggesting 'carryover effects' of algal food quality on carnivores (larval fish) via effects on herbivore (zooplankton) quality. Benthic (tadpole) production was primarily explained by primary production rate, suggesting food quantity rather than quality drives their production. However, benthic FCE was also highest at low light/high nutrients and was significantly correlated with food quality. The stronger effect of food quality in mediating pelagic compared to benthic efficiencies, is consistent with differences in the stoichiometric mismatches between algae and consumers. Pelagic FCE and HEP were more likely to be P‐limited, whereas benthic FCE was more likely N‐limited. This study is the first to examine both pelagic and benthic FCE within the same system, and highlights the importance of differential consumer needs in determining how food quality affects energy transfer efficiency.